Abdome agudo e Síndrome de Fitz-Hugh-Curtis - Curvo, Luiza; Fernández Moreira, Laís; de Paula Adário Landim, Maria Eduarda; Camargo de Jesus, Eliane (Caminhos da Clínica, 2025)
Relato de caso sobre abdomen agudo e Síndrome de Fitz-Hugh-Curtis